2021
DOI: 10.3390/molecules26237168
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Potential of Synthetic Mono-Carbonyl Curcumin Analogs Assessed by Molecular Docking Studies

Abstract: Cognitive decline in dementia is associated with deficiency of the cholinergic system. In this study, five mono-carbonyl curcumin analogs were synthesized, and on the basis of their promising in vitro anticholinesterase activities, they were further investigated for in vivo neuroprotective and memory enhancing effects in scopolamine-induced amnesia using elevated plus maze (EPM) and novel object recognition (NOR) behavioral mice models. The effects of the synthesized compounds on the cholinergic system involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 38 publications
3
23
0
Order By: Relevance
“…Among the fractions, promising effects were produced by SlMo-Chl at 75 and 150 mg/kg body weight doses, compared to the amnesic group that was found to be 65.18 ± 2.61% ( p ˂ 0.001, n = 6) and 69.51 ± 2.71% [F (14.75) = 32.25, p ˂ 0.001, n = 6) correspondingly. The results obtained in this study are in accordance with previously reported studies [ 34 , 35 ]. It could be suggested from the obtained results that the extract at the tested dose could be helpful in reinstating the memory deficit in the experimental animals.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Among the fractions, promising effects were produced by SlMo-Chl at 75 and 150 mg/kg body weight doses, compared to the amnesic group that was found to be 65.18 ± 2.61% ( p ˂ 0.001, n = 6) and 69.51 ± 2.71% [F (14.75) = 32.25, p ˂ 0.001, n = 6) correspondingly. The results obtained in this study are in accordance with previously reported studies [ 34 , 35 ]. It could be suggested from the obtained results that the extract at the tested dose could be helpful in reinstating the memory deficit in the experimental animals.…”
Section: Resultssupporting
confidence: 94%
“…Y-maze test was performed following the reported methodology [ 34 , 35 , 36 ]. Y-maze is a Y shaped apparatus having three arms, arbitrarily named A, B, and C. Each arm has a length of 20 cm, with a height of 15.5 cm and 6 cm in width, oriented at an angle of 120° from the two others.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Behavioral tasks on the Y-Maze Paradigm and “NOD” tasks were conducted in the 5th week of study to determine learning and memory functions. The apparatus arena was cleaned with 70% ethanol during the inter-trial interval to prevent a confounding error due to the influence of odor [ 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Neurodegenerative disorders are a growing public health problem due the rising incidence and low effectiveness of current treatments [ 1 , 2 ]. Alzheimer’s disease is one of the most common age-related irreversible and progressive neurodegenerative disorders characterized by dementia, memory loss, a decline in language skills, and cognitive impairment with aging.…”
Section: Introductionmentioning
confidence: 99%